Coping styles within the family system in the chronic phase following acquired brain injury: its relation to families' and patients' functioning. - Wolters Gregório, Gisela; Stapert, Sven; Brands, Ingrid; van Heugten, Caroline M. (Journal of Rehabilitation Medicine, 2011)
OBJECTIVE: To investigate how the functioning of family members and the coping styles they use are related to the psychosocial functioning both of the family members and of the person who has sustained a brain injury. DESIGN: Cross-sectional study. SUBJECTS: Primary caregivers (n = 61) and other family members (n = 15) of 61 patients with brain injury. METHODS: Primary caregivers completed the Utrecht Coping List, the Life Satisfaction Questionnaire 9, and the Caregiver Strain Index. All family members completed the Family Assessment Device. Data for the patients were collected retrospectively. RESULTS: Primary caregivers who had a preference for passive coping styles reported that they experienced a lower level of family functioning, a lower quality of life, and a higher strain. Neither the coping styles nor the psychosocial outcomes of the primary caregivers were significantly associated with patients' self-reported quality of life. Furthermore, there was no correlation between the level of family functioning and a patient's quality of life. CONCLUSION: Coping styles of caregivers are important determinants for their own psychosocial functioning, but not for patients' psychosocial functioning, although causality cannot be inferred. To enhance caregivers' psychosocial functioning, rehabilitation should focus on changing their coping styles into ones that are less passive. Furthermore, distinct or additional interventions may be needed to change the patient's coping style.